2017
DOI: 10.1186/s12936-017-1750-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the utility of a symptom-based algorithm for identifying febrile patients for malaria diagnostic testing in Senegal

Abstract: BackgroundMalaria rapid diagnostic tests (RDTs) enable point-of-care testing to be nearly as sensitive and specific as reference microscopy. The Senegal National Malaria Control Programme introduced RDTs in 2007, along with a case management algorithm for uncomplicated febrile illness, in which the first step stipulates that if a febrile patient of any age has symptoms indicative of febrile illness other than malaria (e.g., cough or rash), they would not be tested for malaria, but treated for the apparent illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Malaria occurrence varies between weeks and years is Sussundenga. This pattern was also reported in Chimoio, Mozambique and other regions in the world [23,28,29]. This study identi ed three malaria clusters of malaria occurrence for under ve age categories.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Malaria occurrence varies between weeks and years is Sussundenga. This pattern was also reported in Chimoio, Mozambique and other regions in the world [23,28,29]. This study identi ed three malaria clusters of malaria occurrence for under ve age categories.…”
Section: Discussionsupporting
confidence: 74%
“…In Chimoio a similar study indicated and ARIMA (2,1,0) (2,1,1) model with the goodness of t of 72.5 % [12]. Similar studies were carried out in Ghana, Afghanistan, India, Ghana, Zambia, South Africa and Senegal and Nigeria using monthly data with comparable results [7,8,9,10,26,29].…”
Section: Discussionsupporting
confidence: 55%
“…Malaria testing of all febrile patients is a critical, early step of malaria case-management [35] which if not systematically performed leads to missed malaria diagnosis both in high and low transmission settings [51][52][53][54]. Low malaria testing rates of fevers have been commonly reported as one of the weakest components of outpatient malaria case-management despite the testing readiness at health facilities [10,16,22,26,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation conducted in 2013-2014 found that this approach missed an unacceptably high proportion of malaria cases, particularly among children younger than 5 years. 26 As a result, in June 2014, the NMCP issued guidance to test all febrile children younger than 5 years throughout the year, expanding to include all febrile patients older than 5 years during rainy season in 2015, and all febrile patients regardless of age or transmission season in mid-2017. Although the crude testing proportion appears to have plateaued since 2015 indicating no increase in testing, the steady increase in the corrected testing proportion suggests that, in fact, testing practices have continued to improve.…”
Section: Discussionmentioning
confidence: 99%